Creep, shrinkage and elastic modulus data of Malaysian concrete - Omar, Wahid; Makhtar, Ahmad Mahir; Tan, Pui Lai; Omar, Roslina; Ng, Ming Kwong (Faculty of Civil Engineering, 2008)
It has been widely acknowledged that creep and shrinkage of concrete are greatly influenced by the surrounding ambient. In spite of various research carried out to investigate the phenomena, little were conducted on time-dependent deformation for concrete in tropical climate. Locally, most creep and shrinkage predictions are obtained by referring to foreign design codes developed in temperate climate countries, risking inaccurate predictions. Therefore this research is dedicated to determine the magnitude of time-dependent deformation of concrete in the tropical climate. The objectives are to systematically collect creep and shrinkage data under the influence of tropical climate and to empirically develop a set of modification factors based on the best prediction model. Time-dependent deformation tests were carried out on standard specimens and on reinforced concrete columns and prestressed concrete beams under laboratory-controlled environment with temperature and relative humidity (RH) of 27±2oC and 50±4% respectively, and natural tropical ambient. On site monitoring of pre-camber of post-tensioned prestressed beams was also carried out. The experimental data were assessed against various existing creep and shrinkage models such as Eurocode 2, ACI 209, B3 Model, CEB-FIP 1990, and Australian Standard 3600 in order to determine the best prediction for tropical concrete. The results show that time-dependent deformation of HSC in the tropical climate is significantly lower than most of the prediction by foreign standard codes. Based on statistical analysis, Eurocode 2 is identified as the best model for tropical concrete and thus chosen as reference model for development of modification factors. Through empirical analysis, modification factors named as TROPCS which stands for ‘Tropical Creep and Shrinkage’ is introduced. Statistically, the prediction with adoption of TROPCS to Eurocode 2 model results in better accuracy. The coefficient of variation for prediction with TROPCS is at an average of 10.0% for creep and at 21.1% for shrinkage. Validations on the accuracy of TROPCS on structural members were conducted through the results of structural deformation. The results prove that the prediction with TROPCS factors is better than the prediction by EC 2 with the average coefficient of variation for TROPCS predictions on structural members at 12.5%, as compared to the coefficient of variation by EC 2 at 14.8%. The TROPCS modification factors are proposed to be included in the National Annex of Malaysian version of Eurocode 2 as an optional reference.